2014
DOI: 10.1016/j.repc.2014.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular septal defect in children and adolescents in Angola: Experience of a tertiary center

Abstract: The study shows that VSD is the most common CHD in childhood, the diagnosis is made late and almost half of VSDs are associated with other CHDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 11 publications
5
12
0
Order By: Relevance
“…In a survey conducted amongst public school children in Mozambique, Marijon, et al found a prevalence of 2.3 in 1000 of which 80% were recently discovered [20]. In another African population, researchers in Angola, showed VSD and TOF as the most frequent acyanotic and cyanotic heart diseases constituting 30% and 8.6% respectively [21]. In the Middle East, Rahim et al found a prevalence of 12.3 per 1000 live births with a variant pattern compared to other studies as ASD was more frequent followed by TOF, PDA, shunts and VSD in decreasing order [22].…”
Section: Discussionmentioning
confidence: 99%
“…In a survey conducted amongst public school children in Mozambique, Marijon, et al found a prevalence of 2.3 in 1000 of which 80% were recently discovered [20]. In another African population, researchers in Angola, showed VSD and TOF as the most frequent acyanotic and cyanotic heart diseases constituting 30% and 8.6% respectively [21]. In the Middle East, Rahim et al found a prevalence of 12.3 per 1000 live births with a variant pattern compared to other studies as ASD was more frequent followed by TOF, PDA, shunts and VSD in decreasing order [22].…”
Section: Discussionmentioning
confidence: 99%
“…In Angola, <5% of CHD cases are diagnosed before 30 days of life. 2,3 In Mozambique, approximately 50% of patients were diagnosed with a cardiac malformation at >2 years of age. 1 A recent national Nigerian pediatric cardiac registry showed that only 14% of diagnoses occurred before 30 days of life.…”
Section: Commentmentioning
confidence: 99%
“…The care of patients with congenital heart disease (CHD) in low-income countries has improved, leading to increased survival and better quality of life. [1][2][3][4][5] Despite this progress, the postoperative care and mortality and morbidity rates of complex CHD remain challenging. 1,3,4 Single ventricle physiology, one of the main complex CHD types, requires early detection and referral to a pediatric cardiac center.…”
Section: Introductionmentioning
confidence: 99%
“…2,[13][14][15][16][17] In the present study, all patients were less than three months of age at the moment of diagnosis and treatment, which is unusual in developing countries. [21][22][23] Until 2011, in Angola, children with CHD could not be treated in the country and were sent to referral centers in Europe and South Africa. Mean age at diagnosis of CHD was two years.…”
Section: Commentsmentioning
confidence: 99%
“…As the number of diagnosis largely outnumbered expatriation logistics, the number of children waiting for cardiac surgery was more than 1,000. 21 The installation of a tertiary pediatric cardiac center in Luanda (2011) was the result of a joint Angolan-Portuguese venture under the auspices of the Angolan Ministry of Health. Organization of a patient referral system, political commitment, and commitment of Angolan and Portuguese professionals were instrumental in achieving these results.…”
Section: Commentsmentioning
confidence: 99%